Relationship between interleukin-6 (IL-6) levels and chest X-ray severity scoring in COVID-19 patients - Kardiasyah, Alzi; Syarani, Fajrinur; Bihar, Syamsul; Lubis, Netty D.; Mutiara, Erna; Syahputra, Hafid (Narra J, 2024)
The severity of coronavirus disease 2019 (COVID-19) may be measured by interleukin-6 (IL-6) and chest X-rays. Brixia score of the chest radiographs is usually used to monitor COVID-19 patients’ lung problems. The aim of this study was to demonstrate the relationship between IL-6 levels and chest radiographs (Brixia score) that represent COVID-19 severity. A retrospective cohort study was conducted among COVID-19 patients who had a chest X-ray and examination of IL-6 levels at H. Adam Malik General Hospital, Medan, Indonesia. A multinomial logistic regression analysis was conducted to evaluate the association between IL-6 levels and the severity of the chest radiograph. A total of 76 COVID-19 patients were included in the study and 39.5% of them were 60–69 years old, with more than half were female (52.6%). A total of 17.1%, 48.7%, and 34.2% had IL-6 level of <7 pg/mL, 7–50 pg/mL and >50 pg/mL, respectively. There were 39.5%, 36.8% and 23.7% of the patients had mild, moderate and severe chest X-rays based on Brixia score, respectively. Statistics analysis revealed that moderate (OR: 1.77; 95% CI: 1.05–3.32) and severe (OR: 1.33; 95% CI: 1.03–3.35) lung conditions in the chest X-rays were significantly associated with IL-6 levels of 7–50 pg/mL. IL-6 more than 50 pg/mL was associated with severe chest X-ray condition (OR: 1.97; 95% CI: 1.15–3.34). In conclusion, high IL-6 levels significantly reflected COVID-19 severity through chest X-rays in COVID-19 patients.